Construction of evaluation Framework for classroom Teaching Reform of students Empowered by Digitalization - Zhu, Yuzhi (Pacific International Journal, 2024)
The pervasive infiltration of digital technologies into education has brought both opportunities and challenges for empowering students through classroom teaching reforms. However, research evaluating the impacts of such reforms on multidimensional student empowerment remains limited. This mixed methods study aimed to develop a comprehensive evaluation framework to assess the outcomes of digital classroom reforms across five empowerment dimensions: engagement, motivation, autonomy, collaboration, and digital literacy. The sample included 300 college students and 20 teachers from three schools that have implemented technology-driven instructional reforms in the past two years. Quantitative survey data and qualitative insights from interviews and observations were integrated to evaluate the reforms. Results revealed increased student interest, confidence, self-direction and teamwork abilities. However, some forms of technology integration decreased quality student-teacher interactions. Over-reliance on educational technologies was linked to distractions and diminished personalized guidance. The evaluation framework provides a robust tool to systematically identify strengths and weaknesses of reforms from multiple stakeholder perspectives. It enables educators to refine digitally-enhanced pedagogies to optimize empowering effects. Insights gained showcase the importance of balancing student-driven active learning with teacher facilitation and mentorship. Implementation factors such as digital citizenship modeling and scaffolding self-directed learning skills are also key to ensuring technologies empower rather than distract. The study contributes an evidence-based framework to inform the design of classroom teaching reforms that leverage digitalization to fully develop motivated, engaged learners equipped to thrive in the century.